Linking Action Research to Response to Intervention (RtI): The Strategy Implementation Project - David Hoppey (Networks: An Online Journal for Teacher Research, 2013)
This paper showcases how one teacher preparation program embedded action research within the Response to Intervention (RtI) model. This integration helped preservice teachers gain a deeper knowledge of RtI key concepts and pedagogical decision making for meeting diverse students’ needs. Examples from a course assignment are provided to demonstrate how an action research framework helped cultivate the professional knowledge and skills needed to understand and successfully implement the RtI decision-making process. A brief discussion and implications for teacher preparation programs are also shared.